Structural and contextual model of a concept - Yaremko, Yaroslav; Luzhetska, Natalia; Kushlyk, Oksana; Matskiv, Petro; Senkiv, Svitlana (Linguistics and Culture Review, 2021)
The central notion of the cognitive linguistics “concept” has been defined in a number of ways thus the authors suggest the unique way to treat its structure and content. The article provides the interpretation variability of a concept taking into account two approaches – lingual and cultural and semantic and cognitive one which construct cognitive and discourse vector lying in the dimension of both cognition and communication. Whereas the content of a concept is carried out via multidimensional (thinking and speaking in the first place) activity of a person the work considers its structure (imaginary, notional, axiological and adorative (secret) components being in a harmonious unity with the structure of a communicative personality (pragmatic-motivational, cognitive, verbal-semantic, transcendental levels). Concept is a coherent ethnic and mental unit possessing complex four-level structure. It implies interaction and interrelation between a concept and communicative personality, their two-side hierarchical connection particularly using spiritual halo. The following research methods were used in the work: observation, induction and deduction, analysis and synthesis, modelling method, which are necessary for the objective scientific definition of the subject in question; cognitive and discourse analysis. The article provides stratification of a concept in connection with the structure of communicative personality.